Unveiling the potential of metaverse in project management education - Tufan Özsoy (International Journal of Information Systems and Project Management, 2025)
The Fourth Industrial Revolution (4IR), driven by technological advancements such as Artificial Intelligence (AI), has transformed industries, reshaping the skills required in the workforce. Project management education must adapt to these changes by integrating innovative teaching methods to prepare future professionals. This study explores the potential of the metaverse, an immersive virtual environment, to revolutionize project management education. By offering interactive, real-time simulations and personalized learning experiences, the metaverse enables learners to engage with complex project management scenarios beyond the limitations of traditional classrooms. This research combines a literature review and qualitative analysis of project managers' perspectives to assess the benefits and challenges of incorporating the metaverse into educational curricula. The findings highlight the potential for enhanced engagement and the barriers to adoption, including technology access and learning curve concerns. The study concludes by proposing future research directions and addressing limitations regarding the scalability and effectiveness of metaverse-driven education in diverse project management contexts.